Regional Heterogeneity of Perivascular Adipose Tissue: Morphology, Origin, and Secretome - Li, Xinzhi; Ma, Zhongyuan; Zhu, Yi Zhun (Frontiers in Pharmacology, 2021)
Perivascular adipose tissue (PVAT) is a unique fat depot with local and systemic impacts. PVATs are anatomically, developmentally, and functionally different from classical adipose tissues and they are also different from each other. PVAT adipocytes originate from different progenitors and precursors. They can produce and secrete a wide range of autocrine and paracrine factors, many of which are vasoactive modulators. In the context of obesity-associated low-grade inflammation, these phenotypic and functional differences become more evident. In this review, we focus on the recent findings of PVAT’s heterogeneity by comparing commonly studied adipose tissues around the thoracic aorta (tPVAT), abdominal aorta (aPVAT), and mesenteric artery (mPVAT). Distinct origins and developmental trajectory of PVAT adipocyte potentially contribute to regional heterogeneity. Regional differences also exist in ways how PVAT communicates with its neighboring vasculature by producing specific adipokines, vascular tone regulators, and extracellular vesicles in a given microenvironment. These insights may inspire new therapeutic strategies targeting the PVAT.